Analysis of emissions during the combustion of pellets in boiler units - Ivasenko, Vitaliy; Primisky, Igor (Technology audit and production reserves, 2022)
The object of research is the technological process of burning pellets in boilers. Using solid fuel boilers on pellets for heat production, they are trying to reduce dependence on hydrocarbon energy resources. Often such boilers are installed for autonomous heating of schools and other communal facilities. One of the most problematic areas is the analysis of the environmental impact when using pellets as a fuel for municipal boiler houses in urban areas. Boilers operating on solid fuels are characterized by a larger range of pollutants, as well as large values of concentrations emitted through the chimney. In the course of the research, instrumental measurement tools were used, which made it possible to obtain the value of the concentrations of pollutants in the emissions from the chimneys of boilers. In particular, the average maximum concentrations of the main pollutants were: nitrogen dioxide – 271.78 mg/m3, carbon emissions – 1935.44 mg/m3, sulfur dioxin – 13.37 mg/m3, suspended solids, undifferentiated in composition (dust, ash) – 93.2 mg/m3. Using the data of instrumental measurements according to the method of calculating the concentrations of harmful substances in the atmospheric air, a map of the dispersion of emissions was created. Surface concentration fields were plotted on the scatter map, which makes it possible to compare the obtained values with hygienic normative atmospheric air. This makes it possible to determine the distance where the highest value of pollutants from the emission source is recorded. By combining instrumental measurement methods and calculation methods, the volumes and nomenclature of emissions were determined. This made it possible to determine the amount of pollutants per unit mass of burned pellets in the boiler. Using the conducted studies and theoretical calculations for various types of fuel in the production of heat, this will allow assessing their impact on air pollution and reducing the risk of harm to human health.